Operabygningen i Oslo: et økologisk paradoks - Haugdal, Elin (Nordlit, 2011)
This essay discusses the Oslo Opera House building designed by Snøhetta (inaugurated 2008) as one of three monumental buildings in EU's Eco Culture Program and a so called demonstration building for ecological solutions in architecture. The most visible result in the Opera building is a large-scale glass wall with integrated solar cell panels, producing electricity as well as providing sun shading. The real ecological values, however, are hardly to be measured in money or watt, nor in reduced emissions or climatic change. This solar wall is first and foremost putting a strong ecological intention on display.With its giant ecological footprint Snøhetta's building can never be defended within a rational, environmental discourse. It is a contradictory example of sustainable architecture measured up against crucial factors like situatedness, construction and materials, energy consumption and costs. But this spectacular monumental construction which presents a new urban space in a former industrial part of the city, needs to be studied in accordance with deep ecology theories like Félix Guattari's Les trois écologies (1989). Guattari's extended definition of ecology, including sociocultural conditions and human mentality, gives an opportunity to discuss ecology not first and foremost as a rational and ethical challenge in architecture but as an aesthetical.